Individual Differences in Verbal and Spatial Stroop Tasks: Interactive Role of Handedness and Domain - Capizzi, Mariagrazia; Ambrosini, Ettore; Vallesi, Antonino (Frontiers in Human Neuroscience, 2017)
A longstanding debate in psychology concerns the relation between handedness and cognitive functioning. The present study aimed at contributing to this debate by comparing performance of right- and non-right-handers on verbal and spatial Stroop tasks. Previous studies have shown that non-right-handers have better inter-hemispheric interaction and greater access to right hemisphere processes. On this ground, we expected performance of right- and non-right-handers to differ on verbal and spatial Stroop tasks. Specifically, relative to right-handers, non-right-handers should have greater Stroop effect in the color-word Stroop task, for which having strong inter-hemispheric interaction does not seem to be advantageous to performance. By contrast, non-right-handers should be better able to overcome interference in the spatial Stroop task. This is for their preferential access to the right hemisphere dealing with spatial material and their greater inter-hemispheric interaction with the left hemisphere hosting Stroop task processes. Our results confirmed these predictions, thus showing that handedness and the underlying brain asymmetries may be a useful variable to partly explain individual differences in executive functions.